CAD-CAM removable complete dentures: A systematic review and meta-analysis of trueness of fit, biocompatibility, mechanical properties, surface characteristics, color stability, time-cost analysis, clinical and patient-reported outcomes. (October 2021) - Srinivasan, Murali; Kamnoedboon, Porawit; McKenna, Gerald; Angst, Lea; Schimmel, Martin; Özcan, Mutlu; Müller, Frauke
Abstract: Objectives: This review compared Computer-aided designand Computer-aided manufactured (CAD-CAM) and conventionally constructed removable complete dentures (CDs). Data: Seventy-three studies reporting on CAD-CAM (milled/3D-printed) CDs were included in this review. The most recent literature search was performed on 15/03/2021. Sources: Two investigators searched electronic databases [PubMed (MEDLINE), Embase, CENTRAL], online search engines (Google) and research portals. Hand searches were performed to identify literature not available online. Study selection: Studies on CAD-CAM CDs were included if they reported on trueness of fit, biocompatibility, mechanical, surface, chemical, color, microbiological properties, time-cost analysis, and clinical outcomes. Inter-investigator reliability was assessed using kappa scores. Meta-analyses were performed on the extracted data . Results: The kappa score ranged between 0.897–1.000. Meta-analyses revealed that 3D-printed CDs were more true than conventional CDs (p = 0.039). Milled CDs had a higher flexural-strength than conventional and 3D-printed CDs (p < 0.0001). Milled CDs had a higher flexural-modulus than 3D-printed CDs (p < 0.0001). Milled CDs had a higher yield-strength than injection-molded (p = 0.004), and 3D-printed CDs (p = 0.001). Milled CDs had superior toughness (p < 0.0001) and surface roughness characteristics (p < 0.0001) than other CDs . Rapidly-prototyped CDs displayed poor color-stability compared to other CDs (p = 0.029). CAD-CAM CDs d displayed better retention than conventional CDs (p = 0.015). Conventional CDs had a higher strain at yield point than milled CDs (p < 0.0001), and had superior esthetics than 3D-printed (p < 0.0001). Fabrication of CAD-CAM CDs required less chairside time (p = 0.037) and lower overall costs (p < 0.0001) than conventional CDs. Conclusions: This systematic review concludes that CAD-CAM CDs offer a number of improved mechanical/surface properties and are not inferior when compared to conventional CDs. Clinical significance: CAD-CAM CDs should be considered for completely edentulous patients whenever possible, since this technique offers numerous advantages including better retention, mechanical and surface properties but most importantly preserves a digital record. This can be a great advantage for older adults with limited access to dental care.